Wadah SIG BioMECs Basic Phylogenetics and Bioinformatics Methods Workshop / Dr Nor’Aishah Hasan... [et al.] - Hasan, Dr Nor’Aishah; Nawahwi, Mohd Zaini; Zainal Abidin, Dr Nurhamimah; Md Yasin, Dr Ida Muryany; Abd Aziz, Dr Amirul Adli; Ahmad, Dr Nor Monica; Hj. Yaacob, Ilyanie; Hasbullah, Nur Intan (UiTM Cawangan Negeri Sembilan, 2022)
The special Interest Group (SIG) BioMECs achieved another milestone in 2021 by hosting a workshop entitled ‘Basic Phylogenetics and Bioinformatics Methods’. This workshop was held on the 11th November 2021, led by Dr Dzarifah Zulperi, a senior lecturer from the Faculty of Agriculture, Universiti Putra Malaysia (UPM). This workshop marked another important step in our mission to provide a platform for sharing knowledge discourse in targeted fields, namely biotechnology, microbiology and the environment comprehensively to improve the quality and scholarship in the field of science. This paid half- day workshop (from 10 am to 1pm) engaged 67 participants from both local and international via Google meet application. Teaching materials were provided through the designated Google Classroom. This workshop also included discussion and hands-on session on the software and an opportunity to respond to audience generated questions.